2008
DOI: 10.1086/525267
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Skin Contamination in Patients with C. difficile-Associated Disease

Abstract: In a prospective study of 27 patients with Clostridium difficile-associated disease, we found that C. difficile frequently contaminated multiple skin sites, including groin, chest, abdomen, forearms, and hands, and was easily acquired on investigators' hands. Skin contamination often persisted on patients' chest and abdomen after resolution of diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 15 publications
0
62
0
4
Order By: Relevance
“…C. diffi cile can also be cultured from the surfaces of rooms of patients with asymptomatic CDI, albeit to a lesser degree than from the rooms of patients with symptomatic CDI. Additionally; it has been shown that the skin surfaces of patients with CDI diarrhea that resolved 2 weeks before is still contaminated with C. diffi cile that may be transferred to an examining gloved hand ( 177 ). One recommendation is to maintain contact precautions for 48 h aft er diarrhea ceases ( 178 ).…”
Section: Management Of CDI and Co-morbid Conditionsmentioning
confidence: 99%
“…C. diffi cile can also be cultured from the surfaces of rooms of patients with asymptomatic CDI, albeit to a lesser degree than from the rooms of patients with symptomatic CDI. Additionally; it has been shown that the skin surfaces of patients with CDI diarrhea that resolved 2 weeks before is still contaminated with C. diffi cile that may be transferred to an examining gloved hand ( 177 ). One recommendation is to maintain contact precautions for 48 h aft er diarrhea ceases ( 178 ).…”
Section: Management Of CDI and Co-morbid Conditionsmentioning
confidence: 99%
“…Los focos que contribuyen a la diseminación de las esporas en el ambiente hospitalario son diversos. Estudios han demostrado que el personal médico puede actuar como vector de transmisión de esporas de C. difficile 26,45,46 . Recientemente, Landelle y cols.…”
Section: Esporas De C Difficile Como Vector De Transmisiónunclassified
“…47 , observaron que cerca de 25% del personal a cargo del cuidado de pacientes con IACD tenía sus manos contaminadas con esporas de C. difficile debido al no uso de guantes. Los pacientes con IACD son considerados diseminadores de esporas de C. difficile, a través de sus deposiciones, piel y ropa 26,45,46 . Debido a esto, es vital un diagnóstico temprano de los casos de IACD, lo que permite identificarlos oportunamente y aislarlos.…”
Section: Esporas De C Difficile Como Vector De Transmisiónunclassified
“…Do not wear the same pair of gloves for the care of more than one patient (IB). 73,114,123,139,520,941,1021 D. When wearing gloves, change or remove gloves during patient care if moving from a contaminated body site to either another body site (including non-intact skin, mucous membrane or medical device) within the same patient or the environment (II). 72,123,139 E. The reuse of gloves is not recommended (IB).…”
Section: Use Of Glovesmentioning
confidence: 99%